2022
DOI: 10.1097/cej.0000000000000756
|View full text |Cite
|
Sign up to set email alerts
|

Women’s attitudes towards healthy life awareness and breast cancer screening during the coronavirus disease 2019 pandemic: a cross-sectional descriptive study

Abstract: Background In the COVID-19 pandemic, fear of coronavirus infection has caused individuals to hesitate to access medical services and postpone their participation in diagnostic and screening programs. With this research, it was aimed to examine the relationship between women’s wellness awareness and attitudes towards breast cancer screening during the COVID-19 pandemic. Methods The descriptive cross-sectional type research was conducted between 30 January 2021 and 30 July 2021. The sample of the study consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 24 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…[2][3][4]18 in such a way that physical distancing can be maintained, prevent crowding, introduce an appointment system, individually assess COVID-19 symptoms before the examination, conduct rapid tests for COVID-19 detection, and perform sterilization and disinfection treatments at regular intervals. 19 It has been reported that making the screening environment safe for those who do not undergo screening or delay it due to fear of infection can increase their willingness to participate in the screening process. 13,18 Currently, a survey regarding people's plans to receive cancer screening in 2021 has shown a decrease in fear of COVID-19 infection and an increase in the number of people who want to receive it.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[2][3][4]18 in such a way that physical distancing can be maintained, prevent crowding, introduce an appointment system, individually assess COVID-19 symptoms before the examination, conduct rapid tests for COVID-19 detection, and perform sterilization and disinfection treatments at regular intervals. 19 It has been reported that making the screening environment safe for those who do not undergo screening or delay it due to fear of infection can increase their willingness to participate in the screening process. 13,18 Currently, a survey regarding people's plans to receive cancer screening in 2021 has shown a decrease in fear of COVID-19 infection and an increase in the number of people who want to receive it.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in the results of an awareness survey, which found that individual and workplace examinations are preferred over group examinations, which carry a relatively high risk of infection. Therefore, it is important to install personal protective equipment in examination rooms, arrange waiting rooms in such a way that physical distancing can be maintained, prevent crowding, introduce an appointment system, individually assess COVID‐19 symptoms before the examination, conduct rapid tests for COVID‐19 detection, and perform sterilization and disinfection treatments at regular intervals 19 . It has been reported that making the screening environment safe for those who do not undergo screening or delay it due to fear of infection can increase their willingness to participate in the screening process 13,18 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations